2015
DOI: 10.1074/jbc.m114.618595
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Insight into the Carbohydrate Receptor Binding of F4 Fimbriae-producing Enterotoxigenic Escherichia coli

Abstract: Background: F4 fimbriae produced by enterotoxigenic Escherichia coli mediate attachment to eukaryotic host receptors. Results: The structure of lactose bound to the F4 fimbrial adhesin FaeG ad was elucidated. Conclusion: Lactose interacts at a subdomain grafted on the FaeG ad core domain. Significance: The co-complex structure explains the finely tuned receptor specificity of F4 ad fimbriae; additionally, the carbohydrate binding site differs among FaeG variants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Recent studies characterized some of the porcine intestinal carbohydrate receptor moieties interacting with the F4 fimbriae (162). Crystal structure comparisons of the FaeG variants and of the FaeG ad -lactose complex suggested different variant-specific binding pockets with a potential involvement of conformational changes for the adhesion process (163). Noticeably, all the intestinal ceramides that act as receptor for the F4, F5 and F6 fimbriae need to be hydroxylated (140, 162, 164, 165), indicating the importance of the lipid moiety in the binding properties of gangliosides with short carbohydrate chains.…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…Recent studies characterized some of the porcine intestinal carbohydrate receptor moieties interacting with the F4 fimbriae (162). Crystal structure comparisons of the FaeG variants and of the FaeG ad -lactose complex suggested different variant-specific binding pockets with a potential involvement of conformational changes for the adhesion process (163). Noticeably, all the intestinal ceramides that act as receptor for the F4, F5 and F6 fimbriae need to be hydroxylated (140, 162, 164, 165), indicating the importance of the lipid moiety in the binding properties of gangliosides with short carbohydrate chains.…”
Section: Adhesins and Host Receptorsmentioning
confidence: 99%
“…Moreover, the size and structure of the galactose‐binding site resemble those in Myf and Psa (Supporting Information Fig. S11); for example, in the crystal structure of the FaeG‐lactose complex, the protein interacts with the galactose residue, which also lies flat on the surface of an aromatic side chain (Moonens et al ., ). Hence, it is not surprising that Y. enterocolitica , a strictly enteric pathogen, developed a similar carbohydrate binding specificity.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis was confirmed by Moonens et al, they found that F4ad FaeG interacts via its D′‐D″‐α 1‐α 2 binding domain with the minimal galactose binding epitope, two short amino acid stretches Phe150–Glu152, and Val166–Glu170 are the key residues in the galactose–FaeG interaction. This crucial D′‐α 1 loop are lacking in the ab and ac variants and resulting in different structural and adhesive properties .…”
Section: Discussionmentioning
confidence: 99%